Epistemic Justice as a Virtue of Social Institutions - Anderson, Elizabeth (Social Epistemology, 2012)
In Epistemic injustice, Miranda Fricker makes a tremendous contribution to theorizing the intersection of social epistemology with theories of justice. Theories of justice often take as their object of assessment either interpersonal transactions (specific exchanges between persons) or particular institutions. They may also take a more comprehensive perspective in assessing systems of institutions. This systemic perspective may enable control of the cumulative effects of millions of individual transactions that cannot be controlled at the individual or institutional levels. This is true not only with respect to the overall distribution of such goods as income and wealth, but also with respect to the goods of testimonial and hermeneutical justice. Cognitive biases that may be difficult for even epistemically virtuous individuals to correct on their own may be more susceptible to correction if we focus on the principles that should govern our systems of testimonial gathering and assessment. Hence, while Fricker’s focus on individual epistemic virtue is important, we also need to consider what epistemic justice as a virtue of social systems would require. My paper will indicate some directions forward on this front, focusing on the need for integration of diverse institutions and persons engaged in inquiry.
Keywords: approches et analyses; biais cognitifs; capitalisme; cours; cycles supérieurs; discipline; droits des personnes; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; justice épistémique; philosophie; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Cerveau, hormones et sexe : des différences en question - Cossette, Louise (Les éditions du remue-ménage, 2012)
Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d’ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l’information diffusée tient davantage du préjugé, du parti pris idéologique, que d’une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd’hui encore ?C’est de ce constat, et d’un certain sentiment d’exaspération, qu’est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S’appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l’orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d’auteures féministes. Il ne s’agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ? Des textes de Line Chamberland, professeure au département de sexologie de l’UQAM et titulaire de la Chaire de recherche sur l’homophobie de l’UQAM ; Louise Cossette, professeure au département de psychologie de l’UQAM et membre de l’Institut de recherches et d’études féministes (IREF) de l’UQAM ; Chantal Maillé, professeure à l’Institut Simone de Beauvoir à l’Université Concordia et Catherine Vidal, neurobiologiste, directrice de recherche à l’Institut Pasteur de Paris.
Keywords: Brain; Human behavior; LGBTQIA2+; Men; Psychology; Sex differences; Sex differences (Psychology); Women; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; genre; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lit3220; premier cycle; psy4910; psychologie; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sexualité; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Relational Knowing and Epistemic Injustice: Toward a Theory of Willful Hermeneutical Ignorance - Pohlhaus, Gaile (Hypatia, 2012)
I distinguish between two senses in which feminists have argued that the knower is social: 1. situated or socially positioned and 2. interdependent. I argue that these two aspects of the knower work in cooperation with each other in a way that can produce willful hermeneutical ignorance, a type of epistemic injustice absent from Miranda Fricker's Epistemic Injustice. Analyzing the limitations of Fricker's analysis of the trial of Tom Robinson in Harper Lee's To Kill a Mockingbird with attention to the way in which situatedness and interdependence work in tandem, I develop an understanding of willful hermeneutical ignorance, which occurs when dominantly situated knowers refuse to acknowledge epistemic tools developed from the experienced world of those situated marginally. Such refusals allow dominantly situated knowers to misunderstand, misinterpret, and/or ignore whole parts of the world.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; histoire et politique; ignorance herméneutique; injustices herméneutiques; injustices épistémiques; justice sociale; patriarcat; philosophie; privilèges; racisme; sciences humaines; systèmes d'oppressions; thématiques; éthique